Hubungan antara Self-Esteem dengan Perilaku Social Loafing pada Mahasiswa Program Studi Teknik Informatika di Universitas Bina Darma - Salsabila, Hana Azka; Hurriyati, Dwi (Jurnal Ragam Pengabdian, 2026)
This study aimed to determine the relationship between self-esteem and social loafing behavior among students of the Informatics Engineering Study Program at Bina Darma University, Palembang. Social loafing refers to the tendency of individuals to reduce their effort when working in groups compared to working individually. One of the psychological factors associated with this behavior is self-esteem. This study employed a quantitative correlational research design. The participants consisted of 172 active students from the Informatics Engineering Study Program at Bina Darma University, selected using a probability sampling technique. Data were collected using the Self-Esteem Scale and the Social Loafing Scale, both developed based on relevant theoretical frameworks. Data were analyzed using Pearson's Product Moment correlation. The results showed a significant negative relationship between self-esteem and social loafing (r = –0.462, p < 0.05). These findings indicate that students with higher self-esteem tend to exhibit lower levels of social loafing in group assignments. Conversely, students with lower self-esteem are more likely to demonstrate social loafing behavior. Students with positive self-esteem tend to be more confident, responsible, and actively contribute to group work. This study contributes to a better understanding of the psychological factors influencing students' participation in collaborative learning and may serve as a reference for developing strategies to improve teamwork effectiveness in higher education.